Performance and emission analysis of triple fuelled CI engine utilizing producer gas, biodiesel and diesel: An optimization study using response surface methodology - Kumar Singh D.; Raj R.; Tirkey J.V. (My University, 2025)
At present, there is an escalation of electric power demand because of the exponential growth of population and rapid industrialization. Literature reveals that a gasification-based captive power plant is one of the suitable alternatives. In the utilization phase, there must be a balance between power and exhaust emission for economic and environment control; however, there is a gap in such investigation, especially with triple fuel mode in gasifier-engine integration. Therefore, the present work deals with the gasification of waste Madhuca longifolia biomass for producer gas generation and simultaneously induction of PG, Diesel, and Safflower biodiesel in the triple fuel CI engine. The oil output from safflower seed and the biodiesel yield obtained were 26 % and 91 %, respectively. To enhance the gasifier-engine performance, the main objective of this analysis is to conduct a parametric experiment and optimization of operating variables. RSM was employed to optimize the input parameters (equivalence ratio, compression ratio, and Engine load) for the best response of output parameters. RSM results indicates that the optimum magnitude of independent parameters was 0.2 ER, 17.2 CR, and 73.4 % EL, and respective outputs are 2.49 kW BP, 27.57 % BTE, 3.31 kg/kWh BSFC, and emission 0.0081 vol% CO, 8.60 ppm-UHC, 1.53 vol% CO2, and 182.32 ppm NOx with the overall desirability 0.49. Thus, RSM results could be applied satisfactorily to an integrated gasification and triple-fuelled mode CI engine with optimum conditions. Moreover, the projection of the present work will positively provide a direction for the implication to users and further research progress. © 2022 Elsevier Ltd